The influence of Sharia implementation, financing access, and managerial capacity on MSME performance in Medan City, Indonesia - Hasibuan, Muhammad Zulkifli; Ramon, Herdi; Samio, Samio; Nurjannah, Nurjannah; Rijal, Rijal (Universitas Islam Indonesia, 2026)
IntroductionMicro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, contributing significantly to national income and employment. Within this sector, Shariah-compliant MSMEs have emerged as strategic actors that integrate ethical, transparent, and socially responsible business principles aligned with Islamic law. However, limited empirical research has analyzed how Shariah implementation, access to Shariah-based financing, and managerial capacity collectively influence MSME performance, particularly at the city level in Medan.ObjectivesThis study aims to examine the effects of Shariah implementation, access to Shariah-compliant financing, and managerial capacity on MSME performance in Medan, Indonesia. It further investigates the mediating role of managerial capacity in translating Shariah compliance into business growth and employment generation, providing theoretical and practical insights into the development of Shariah-based MSMEs.MethodA mixed-methods sequential explanatory design was employed. The quantitative phase involved a survey of 389 Shariah-compliant MSMEs across key sectors in Medan, analyzed using multiple regression and bootstrap mediation tests. The qualitative phase comprised 20 semi-structured interviews to explore managerial experiences and ethical practices. Triangulation ensured reliability and validity of results, while thematic analysis supported contextual interpretation.ResultsThe findings indicate that Shariah implementation, access to Shariah financing, and managerial capacity each have significant positive effects on MSME revenue and employment growth. Managerial capacity partially mediates the relationship between Shariah implementation and business performance, underscoring its central role in operationalizing ethical values. Qualitative evidence reveals that ethical governance and financial literacy enhance innovation, resilience, and stakeholder trust among Shariah-compliant MSMEs.ImplicationsThe study demonstrates that integrating Shariah principles with managerial competence strengthens MSME sustainability and competitiveness. Policymakers and financial institutions should expand Shariah-compliant financial access, reinforce managerial training, and promote digital Islamic finance to foster inclusive, ethical entrepreneurship.Originality/NoveltyThis research offers empirical evidence linking Islamic ethical principles with measurable business performance, validating managerial capacity as a mediating mechanism. It contributes to Islamic economic literature by presenting a city-level model for sustainable, value-based MSME development that bridges faith, ethics, and economic growth.